Parenting-Related Social Networking Site Use and Psychological Distress in Parents of Infants: Cross-sectional Study Exploring the Moderating Effects of Loneliness and Parenting Anxiety - Ryuta Onishi (JMIR Publications, 2024)
Abstract BackgroundIn the digital age, social networking sites (SNSs) have revolutionized the approach to parenting. These platforms, widely used to access parenting information and support, affect parents both positively and negatively, with negative effects potentially increasing for those experiencing loneliness or anxiety. ObjectiveThis study examined the relationship between SNS use and psychological distress among parents of young children, controlling for the moderating effects of loneliness and parenting anxiety. We hypothesized that higher SNS use correlates to greater psychological distress, particularly among parents with elevated levels of loneliness or parenting anxiety. MethodsA cross-sectional survey design using a closed web-based questionnaire was employed. Participants included 429 parents (205 mothers and 224 fathers) of children aged 0‐3 years recruited through a web-based survey company in Japan. The majority of the participants were couples, with some living with extended family members. The sample also encompassed individuals in cohabiting partnerships and single parents. The survey included measures of psychological distress, loneliness, parenting anxiety, frequency of SNS use for parenting, and covariates. Analytical models to explain psychological distress included interactions between loneliness or parenting anxiety and SNS use, individually for both fathers and mothers. ResultsFor mothers, a significant interaction effect was determined only between parenting anxiety and SNS use (bPbPbPbβPbβPbβP ConclusionsThe study concluded that the relationship between SNS use and psychological distress among parents of young children is moderated by loneliness and parenting anxiety. The findings highlight the need for tailored approaches to help parents manage SNS use, particularly focusing on those with higher levels of loneliness and parenting anxiety. It is imperative that health professionals provide nuanced guidance to parents on SNS use, considering individual psychological factors and potential gender differences in the impact of SNSs on mental well-being.